Why Latin American nations fail development strategies in the twenty-first century - Pérez Caldentey, Esteban; Vernengo, Matías 1968- (University of California Press, 2017)
"Economic and social development is a major topic of discussion in courses across the social sciences, particularly those focused on Latin America. Many scholars and instructors have tried to pinpoint, explain, and define the problem of underdevelopment in Latin America. New ideas have led to new strategies that have, by and large, failed to reduce income disparity and relieve poverty in the region. Why Latin American Nations Fail brings together leading Latin Americanists from several disciplines to address how and why contemporary development strategies have failed to promote long-term sustainable growth with improved well-being throughout the region. Given the dramatic political turns in contemporary Latin America, this book offers a much-needed explanation and analysis of the factors that must be considered in making sense of development today"...Provided by publisher
Includes bibliographical references and index
Keywords: Economic development -- Latin America -- History; Sustainable development -- Latin America; Misserfolg; Entwicklungsmodell; Wirtschaftsentwicklung; Lateinamerika; Konferenzschrift -- 2015 -- New York